Edoxaban eliminates hypercoagulability evoked by transient temperature changes in human whole blood - Suzuki, Anna; Hamada, Satomi; Oono, Ai; Hasegawa, Yuki; Yamauchi, Yasuteru; Okishige, Kaoru; Hirao, Kenzo; Sasano, Tetsuo (Journal of arrhythmia, 2023)
Background Thrombosis is a common critical complication relating to radiofrequency catheter ablation and cryoablation. There is a possibility that high‐temperature stimulation during radiofrequency ablation or low‐temperature stimulation during cryoablation may affect the coagulability of blood. In this study, we aimed to determine the impacts of transient temperature stimulations on the coagulability of whole blood and to clarify if edoxaban suppressed the hypercoagulability. Methods Citrated blood samples were drawn from 41 healthy subjects. Some blood samples were mixed with tissue factor (TF) and several concentrations of edoxaban (50, 100, and 200 ng/mL). Blood samples were exposed to several temperature stimulations for 1 min: heat stimulation (50°C) or cryostimulation (−20°C), and compared with control (37°C). Repeated cryostimulations or sequential cryo‐ and heat stimulation were also applied. Coagulability of whole blood was measured using a dielectric blood coagulometry. As an index of coagulability, the end of acceleration time (EAT) was used. Results Both heat‐ and cryostimulations significantly shortened the EAT compared to the control, indicating that hypercoagulability was induced by temperature stimulations. Application of TF enhanced and extended the hypercoagulability after the temperature stimulations. Sequential application of cryo‐ followed by heat stimulation further enhanced the hypercoagulability of blood. Application of edoxaban increased the EAT in a concentration‐dependent manner in control condition. Edoxaban at 100 or 200 ng/mL completely suppressed the shortening of EAT evoked by these temperature stimulations. Conclusion Transient temperature stimulations evoked hypercoagulability regardless of cryo‐ or heat stimulation. Edoxaban with 100 ng/mL or more eliminated this temperature‐stimulated hypercoagulability. (Upper) End of acceleration time (EAT), an indicator of whole blood coagulability, was shortened after heat‐ or cryoapplications, indicating temperature change induced hypercoagulability. (Lower) Administration of edoxaban at 100 ng/mL diminished the hypercoagulability induced by temperature stimulation.